MALDI Imaging‐Guided Microproteomic Analyses of Heterogeneous Breast Tumors—A Pilot Study. Issue 1 (15th September 2017) - Alberts, Deborah; Pottier, Charles; Smargiasso, Nicolas; Baiwir, Dominique; Mazzucchelli, Gabriel; Delvenne, Philippe; Kriegsmann, Mark; Kazdal, Daniel; Warth, Arne; De Pauw, Edwin; Longuespée, Rémi
Abstract: Matrix‐assisted laser desorption/ionization (MALDI) imaging is an ideal tool to study intratumor heterogeneity (ITH) and its implication in prognostic stratification of patients. However, there are some drawbacks concerning protein identification. On the other hand, laser microdissection (LMD)‐based microproteomics allows retrieving thousands of protein identifications from small tissue pieces. As a proof of concept, the authors combine these two complementary approaches to analyze heterogeneous regions in breast tumors. Invasive ductal breast cancer FFPE tissue sections from five patients are analyzed by MALDI imaging and the dataset is processed by segmentation. Heterogeneous regions within tumors are processed by LMD‐based microproteomics, in duplicates. Liquid chromatography‐tandem mass spectrometry data are classified by hierarchical clustering. Heterogeneous tissue regions are discriminated on the basis of their actual molecular heterogeneity. The dataset is correlated with MALDI imaging to identify m/z values discriminating heterogeneous regions. The molecular characterization of cell clones in tumors related to bad patient outcome could have great impact for pathology. A combined application of LMD‐based microproteomics and MALDI imaging for ITH studies is presented.